Is "Chronicity" Inevitable for Psychotic Illness? Studying Heterogeneity in the Course of Schizophrenia in Yogyakarta - J. Good, Byron; Raymondalexis Marchira, Carla; Ul Hasanat, Nida; Sofiati Utami, Muhana; Subandi, M.A. (Rutgers University Press, 2010)
Schizophrenia has long been viewed as an almost inevitably chronic and degenerative form of mental illness. This chapter examines the course of schizophrenia-spectrum mental illness in Yogyakarta in Central Java, based on a seven-year longitudinal study that follows a small series of cases of individuals with mental illness and their families. It examines questions about the role of culture in shaping the trajectory of illness over time, as well as the effects of inadequate mental health services on the course of mental illness.